Exercise-induced increases in NT-proBNP are not related to the exercise-induced immune response. Issue 5 (9th January 2008) - Scharhag, J; Meyer, T; Auracher, M; Müller, M; Herrmann, M; Gabriel, H; Herrmann, W; Kindermann, W
Abstract : Objective: To investigate if the exercise-induced immune response contributes to the exercise-induced increase in brain natriuretic peptide (BNP) in healthy athletes. This has previously been speculated, as elevated concentrations of BNP or N-terminal pro brain natriuretic peptide (NT-proBNP) in cardiovascular patients were found to be related to immune reactions and elevations in inflammatory cytokines such as interleukin 6 (IL-6). Methods: Stored serum samples were analysed for NT-proBNP concentrations of 14 healthy endurance athletes (mean age: 25 (SD 5) years; VO2peak 67 (SD 6) ml/min/kg), who had been examined previously for exercise-induced immune reactions and their dependence on carbohydrate supplementation (6 or 12% carbohydrate vs placebo beverages) after three bouts of 4 h cycling at a given workload of 70% of the individual anaerobic threshold. Venous blood samples were taken before, immediately after, and 1 h and 1 day after exercise. Leucocyte subpopulations were determined immediately after blood sampling by flow cytometry. Serum samples for posterior analysis of C-reactive protein (CRP), IL-6, cortisol and NT-proBNP were stored at −80°C. Results: The exercise-induced increases in NT-proBNP (p<0.001) were not related to the exercise-induced immune response, although exercise induced marked (CHOS-dependent) increases in IL-6, CRP, cortisol, leucocytes, neutrophils, monocytes and natural killer cells. Conclusion: It is unlikely that the exercise-induced increases in NT-proBNP or BNP in healthy athletes are caused by the exercise-induced immune response. Therefore, exercise-induced increases in NT-proBNP or BNP in healthy athletes have to be differentiated from increases in cardiovascular patients with systemic inflammation.